Development of a lysine biosensor for the dynamic regulation of cadaverine biosynthesis in E. coli - Mingjie Li; Haorong Chen; Yukun Chen; Pengyu Chen; Shuchun Liu; Shuwen Liu; Tingyi Wen (Microbial Cell Factories)
Abstract Background As one of the most promising monomers of biobased polyamides, cadaverine has wide industrial application prospects. However, in microbial cadaverine fermentation with glucose as the sole carbon source, the impaired coordination between precursor (lysine) utilization and cytotoxic cadaverine accumulation has been identified as the primary bottleneck limiting high-yield biosynthesis. Here, we developed a lysine biosensor in Escherichia coli to dynamically regulate cadaverine biosynthesis. Results In this study, we developed a lysine biosensor based on the lysine transporter protein LysP, the transcription activator CadC, and the GFPuv gene under the control of the P cad promoter. However, the engineered lysine biosensor system had a low dynamic range and a narrow pH operating range. Therefore, a multilevel optimization strategy, which included the introduction of key point mutations and engineered promoter modifications, were introduced to improve the performance of the biosensor, resulting in significant improvements in the dynamic range and lysine response. Moreover, we engineered a cadaverine-producing E. coli strain by increasing the supply of the lysine precursor, overexpressing key cadaverine synthesis genes, and knocking out genes related to metabolic bypass. The lysine biosensor was subsequently implemented to dynamically regulate cadaverine biosynthesis, resulting in a 48.10% increase in the production titre (33.19 g/L) and a 21.2% increase in cell growth compared with those resulting from the strain with constitutive expression. Conclusion This is the first report in which a lysine biosensor constructed in E. coli could dynamically regulate cadaverine synthesis to improve its yield and biomass. This strategy provides new insights into the metabolic engineering of lysine and its derivatives in E. coli.